Faktor-faktor yang Mempengaruhi Kinerja Sistem Informasi Akuntansi (Studi Kasus pada RS. PKU Muhammadiyah Surakarta) - Setiaji, Wilis Adi; , Drs. Atwal Arifin, Akt., M.Si (2017)
This study aimed to examine the effect of user of user involvement in system development, User Training and education programs, top management support and personal technical capability toward the performance of accounting information system. Population in this study is employees in finance and accounting in the PKU Muhammadiyah hospital Surakarta was 41 respondents. Collection data the method used was in questionnaire. The sampling technique used in this study is purposive sampling. Data were analyzed using SPSS version 22.0. The results showed that user training and education programs and top management support affecting the performance of accounting information systems. While the user of user involvement in system development and personal technical capability not affect the performance of accounting information system. For further research can add a research not only in the hospital.